CHARACTERISTICS OF RADIO ATTENUATION COEFFICIENT ON THE SØR RONDARNE ICE SHEET, ANTARCTICA - マエノ, ヒデオ; ウラツカ, セイホ; MAENO, Hideo; URATSUKA, Seiho (National Institute of Polar Research, 1997)
P(論文) The depth-averaged attenuation coefficients are calculated from the echo pattern measurements from internal ice. The attenuation coefficients around the Sør Rondane Mountains, Antarctica were mapped from the 179MHz airborne radio-echo sounder, which made observations during 1986. The map shows a tendency of decreasing attenuation as the surface altitude of the ice sheet increases. This result is interpreted by using the relationship between attenuation coefficients and ice temperature. In addition, a cosine relationship was found between attenuation coefficients and the angle of the radar polarization from the topographic contour. The dynamic range of the variety of the attenuation coefficients is 1.2dB/100m. If the ice flow is perpendicular to the topographic contour, the ice flow direction will be derived from the polarimetric radar observation. departmental bulletin paper